Concrete pumping and spraying a practical guide - Cooke, T. H. (Thomas Telford, 1990)
This work is a demonstration of the commercial viability of concrete pumps and spraying equipment, explaining their advantages over traditional methods of concrete placing. This practical guide gives advice on solutions to common problems safety and training and the operation of concrete pumps.
Keywords: Cement guns.; Cement composites.; Shotcrete.; elektronické knihy; electronic books